Growth phase‐dependent surface properties of Legionella pneumophila and their role in adhesion to stainless steel coated QCM‐D sensors. (1st August 2021) - Ariyadasa, S.; Abeysekera, G.; Billington, C.; Fee, C.; Pang, L.
Abstract: Legionella pneumophila cell surface hydrophobicity and charge are important determinants of their mobility and persistence in engineered water systems (EWS). These surface properties may differ depending on the growth phase of L. pneumophila resulting in variable adhesion and persistence within EWS. We describe the growth‐dependent variations in L. pneumophila cell surface hydrophobicity and surface charge using the microbial adhesion to hydrocarbon assay and microelectrophoresis, respectively, and their role in cell adhesion to stainless steel using a quartz crystal microbalance with dissipation (QCM‐D) monitoring instrument. We observed a steady increase in L. pneumophila hydrophobicity during their lifecycle in culture media. Cell surfaces of stationary phase L. pneumophila were significantly more hydrophobic than their lag and midexponential counterparts. No significant changes in L. pneumophila cell surface charge were noted. Morphology of L. pneumophila remained relatively constant throughout their lifecycle. In the QCM‐D study, lag and exponential phase L. pneumophila weakly adhered to stainless steel surfaces resulting in viscoelastic layers. In contrast, stationary phase bacteria were tightly and irreversibly bound to the surfaces, forming rigid layers. Our results suggest that the stationary phase of L. pneumophila would highly favour their adhesion to plumbing surfaces and persistence in EWS.